Due usi italiani di enunciazione - La Mantia, Francesco (Rivista Italiana di Filosofia del Linguaggio)
This article examines two uses of the word enunciation in some recent contributions of the italian semiotics: a) “enunciation” as activation of open semantic potentials (VIOLI 2003) ; b) “enunciation” as modulation of local encyclopedic sections (PAOLUCCI 2010). Thanks to the theoretical resources of two fundamental research programs as Benveniste’s linguistics (LEB) and Culioli’s theory of predicative and enunciative operations (TOPE), we try to demonstrate that these uses are variants of the same general idea, i.e. “actualization” of encyclopedic virtualities. In the last section of the paper, we formulate some questions that remain open in the context of this investigation.